Evaluation of the Status of Women in Development in Islamic Countries - Abdolmajid Ahangari; seyed aziz arman; Ahmad Sallahmanesh; Masomeh Rezaean (توسعه اجتماعی, 2023)
Regarding the importance of the concept of human development as the main objective of development and consequently, the reduce gender inequality and also, importance of the potential role of women in the process of economic growth and development, over the past few decades, economists and international organizations including the United Nations, have emphasized the status and contribution of women in development process as one of the development criteria. In this research, the status of women in the development process in Islamic countries has been evaluated and compared on the base of 26 selected indicators, using the numerical taxonomy method in 2005 and 2015. The results of the research show that in this period, in the most of Islamic countries, the status of women in development process compared to men has improved, although, the dispersion and inequality among the countries has increased. According to research results, in 2005, women in Qatar and Chad with a development degree of 0.68 and 0.99 and in 2015, in Kazakhstan and Chad, with degree of 0.64 and 1/1, respectively, have the highest and lowest status in development process. By comparing the degree of development of Iran from 0/84 to 0/83 from 2005 to 2015, it can be said that although gender inequality in development in Iran, has slightly reduced, its ranking in among 33 Islamic countries has fallen from 15 to 17. Also, the coefficient of dispersion in the Islamic countries in gender inequality in development has increased from 0.88235 in 2005 to 0.11219 in 2015.